The correlation with abnormal fetal outcome and a high level of amniotic fluid alpha-fetoprotein in mid-trimester - Tian-Jeau Huang; Chih-Ping Chen; Chen-Ju Lin; Fang-Tzu Wu; Shin-Wen Chen; Shih-Ting Lai; Zhi-Jun Chen (Elsevier, 2023)
Objective: To evaluate the correlation of high levels [>2.0 multiples of median (MoM)] of amniotic fluid alpha-fetoprotein (AFAFP) in midtrimester with abnormal fetal outcome. Materials and methods: We retrospectively studied 6245 pregnant women with singleton pregnancy who had undergone amniocentesis between 15 and 27 weeks' gestation at Mackay Memorial Hospital between January 2014 and June 2020. Fifty-five cases had high AFAFP levels (>2.0 MoM). We investigated the abnormal fetal outcomes. Results: Among the fifty-five cases with high AFAFP levels (>2.0 MoM), thirty (54.5%) had fetal chromosomal abnormalities, major structural abnormalities, and/or adverse obstetric events. Eight cases (14.5%) had chromosomal abnormalities including trisomy 21 (3 cases), trisomy 18 (3 cases), mosaic trisomy 18 (1 cases), and mosaic ring 13 (1 case). Seventeen cases (30.9%) had major structural abnormalities including abdominal wall defect (6 cases) and central nervous system (5 cases), gastrointestinal tract (3 cases), cardiovascular (2 cases), and genitourinary tract (2 cases) abnormalities. Fifteen cases (27%) had adverse obstetric events, including preterm delivery (5 cases), intrauterine fetal demise (4 cases), small for gestational age (4 cases), preeclampsia (4 cases), gestational diabetes mellitus (2 cases), gestational hypertension (1 case), preterm prelabor rupture of membrane (1 case), prolonged labor (1 case), and preterm uterine contraction (1 case). Conclusion: A high AFAFP level (>2.0 MoM) in midtrimester can be associated with abnormal fetal outcome, including chromosomal abnormalities, major structural abnormalities, and adverse obstetric events. Women with a prenatal diagnosis of high AFAFP levels (>2.0 MoM) should be alerted of the possibility of abnormal fetal outcomes, and further detailed genetic studies and serial sonographic examinations are recommended.